How do you solve \frac { 5} { x + 3} - 2= \frac { 7} { x + 3}5x+32=7x+3?

1 Answer
Mar 29, 2017

x=-4x=4

Explanation:

Multiply each term by x+3x+3 to get rid of the fraction

cancel(x+3)*5/cancel(x+3)-2(x+3)=cancel(x+3)*7/cancel(x+3)

5-2(x+3)=7

Solve the term that has parenthesis using the distributive property

5-2x-6=7

Group like terms

5-6-2x=7

-1-2x=7

When you take a number or a variable to the other side of an equation, the sign changes.

-2x=7+1

-2x=8

Divide both sides by -2

(cancel(-2)x)/cancel(-2)=8/-2

x=-4